Improving the Production Variables and Designing Innovative Complete Garment Pieces on Seamless Weft Knitting Machine - Doaa Abd Elgawad; Rawia Ali ali; racha Abd el-hady (Maǧallaẗ Al-Turāṯ wa Al-Taṣmīm, 2022)
Six pieces of women's home clothes of different designs were produced using different materials and yarns. Nylon was selected with Lycra material to produce all research samples, with the difference in yarn count, Nylon count 20 (1/20/20) ,40 (1/34/44) and 70 (1/78/68) denier with Lycra count 20 denier All samples and dressed pieces are designed and produced on Seamless Weft Circular machine with Gouge 28 using different designs of executed pieces Laboratory tests were conducted to evaluate the functional properties of the vector wear pieces taking advantage of the capabilities of the used machine and specialized design programs to reach the best production specificationBy conducting a statistical analysis of the result it was found that there is an effect of the difference in yarn count and the executed design on the functional properties of all produced pieces of clothing (cloth thickness (mm) weight per square meter (g/m2) air permeability cm / cm2 Bursting strength (Pa) to reach the best standard specification